Nature connectedness and other transformative qualities associated with pro-environmental attitudes, behaviors, and engagement across scales: the direction of compassion matters - Cecilia U. D. Stenfors; Walter Osika; Luis Mundaca; Silke Ruprecht; Lena Ramstetter; Christine Wamsler (Global Sustainability)
Abstract Non-technical summary This study addresses the challenge of climate change by exploring how psychological qualities and meditation practices may influence pro-environmental behavior among decision-makers, by surveying 185 participants. The research found that meditation practices and compassion toward others are linked to more pro-environmental actions. Nature connectedness emerged as a key factor related to enhanced mindfulness, compassion toward others and self, and environmental efforts. Additionally, pro-environmental efforts at work were related to more engagement across the organization, including management. These findings highlight the potential of integrating personal growth practices into sustainability promoting strategies, suggesting that fostering compassion and mindfulness may support pro-environmental action.